PEMBUATAN PROGRAM REKONSTRUKSI KONTUR CITRA 3D PADA ORGAN MENGGUNAKAN MATLAB 2008a - Siti A'isyah; Kusworo Adi; Choirul Anam (Youngster Physics Journal, 2013)
Program of contour  Reconstruction of 3D imaging at organ has been done. To determine the tumor volume by creating a 3D contour Planning Target Volume (PTV) and organs at risk in head for each image slice. Determination of 3D PTV contour begins with contouring, featuring contour, contour editing and showing PTV and organs at risk in 3D. So that a more accurate determination of radiotherapy dose and the organ at risk dose does not exceed a given tolerance. 3D contour reconstruction algorithm can be displayed on each slice so organ at risk boundary and Planning Target Volume (PTV) that used to radiotherapy treatment can be seen.Keywords: radiotherapy, treatment planning system (TPS), Planning Target Volume (PTV).